A RETROSPECTIVE PICTURE OF PARENTAL ATTITUDES IN INCARCERATED MALE RECIDIVISTS - Lipinski, Stanislaw (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article discusses the issue of perception of parental attitudes in male recidivists compared to the reference group of males without criminal record. Responders answered questions from the PCR questionnaire, regarding the behavior of their mothers and fathers in relation to them, before they were 12 years old. It is a retrospective image of the attitudes of their parents, whose content depends on the global assessment of those attitudes with a strong impact on interpersonal views. A retrospective image of the attitudes of the parents is a kind of cognitive pattern that can influence current perception of the surrounding world. That perception is one of the elements of the assessment of the development of human cognitive structures. The obtained results of particular categories of parental attitudes perception, i.e. loving, rejecting, protecting, and liberal of the father and mother, have been subsequently subjected to statistical analysis. The aim of that analysis was to obtain an answer to the question whether the arithmetic means of those categories differentiated the compared groups in a statistically significant way.